How to tackle the slowdown of potential growth rate in China? - Fang Cai (China Finance and Economic Review, 2015)
Background: The shrinkage of working age population at ages between 15 and 59 after 2010 will end the era of the high-speed economic growth in China. This paper is intended to explore the ways of tackling this slowdown. Methods: By revealing annual growth rate of potential output to drop to 7.2 % in 2011-2015 and 6.1 % in 2016-2020, this paper is to explain the cause of growth rate deceleration and draw policy implications of such slowdown. Results: First, the government should not seek a growth rate above potential rate if they do not intend to see distortions in the economy such as macroeconomic instability, overcapacity, deviation from comparative advantage, and protection of inefficient firms. Second, the potential growth rate can be strengthened through institutions building and reorientation of public policy in various areas in order to spur labor mobility and productivity improvement. Conclusions: This paper suggests to deepen economic reform in order to sustain the necessarily high growth rate of the Chinese economy.
Keywords: 330; Potential growth rate; Diminishing return to capital; Total factorproductivity (TFP)